Robotics and Reproductive Surgery - Estes, Stephanie J.; Waldman, Ian; Gargiulo, Antonio R. (Seminars in Reproductive Medicine, 2017)
Robotic technology applied to laparoscopy augments the armamentarium of the reproductive specialist. Uterine leiomyomas, adenomyosis, endometriosis, adnexal masses, sterilization reversal, and fertility preservation techniques can all be addressed with a robotic surgery skill set. Additionally, new approaches with single site and natural orifice surgery will continue to maximize advanced opportunities for safe, effective, and cosmetically conscious (patient-centered) approaches to surgical care. Enhanced postoperative recovery pathways are fully adaptable to these robotic procedures and improve patient acceptability while controlling costs.
Keywords: robotic surgery; reproductive surgery; minimally invasive surgery; gynecology; infertility